(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Mironenko N. Preparing future teachers of technology to future careers in the discipline "Selected problems of Metrology". The article the features of preparation of future teachers of technologies are examined to future professional activity during the study of discipline «Select questions of metrologi».